2016
DOI: 10.1371/journal.pone.0150025
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life, Self-Efficacy and Enjoyment Keep the Socially Vulnerable Physically Active in Community-Based Physical Activity Programs: A Sequential Cohort Study

Abstract: Physical inactivity is most commonly found in socially vulnerable groups. Dutch policies target these groups through community-based health-enhancing physical activity (CBHEPA) programs. As robust evidence on the effectiveness of this approach is limited, this study investigated whether CBHEPA programs contribute to an increase in and the maintenance of physical activity in socially vulnerable groups. In four successive cohorts, starting at a six-month interval, 268 participants from 19 groups were monitored f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 79 publications
(106 reference statements)
0
11
1
Order By: Relevance
“…In our study, however, no significant association was observed between the average number of steps walked and the lower-limb muscle strength among CLI patients. Moreover, it is generally considered that the amount of physical activity and health-related QOL are strongly correlated with each other 11 ) and that the higher the sense of well-being, the more they are involved in physical activity 12 ) , but no correlation was observed between the number of steps walked and health-related QOL in our study. Patients with CLI need non-weight bearing exercise during the treatment of wound to reduce the burden to the wounded area, which consequently imposes restrictions on their walking.…”
Section: Discussioncontrasting
confidence: 62%
“…In our study, however, no significant association was observed between the average number of steps walked and the lower-limb muscle strength among CLI patients. Moreover, it is generally considered that the amount of physical activity and health-related QOL are strongly correlated with each other 11 ) and that the higher the sense of well-being, the more they are involved in physical activity 12 ) , but no correlation was observed between the number of steps walked and health-related QOL in our study. Patients with CLI need non-weight bearing exercise during the treatment of wound to reduce the burden to the wounded area, which consequently imposes restrictions on their walking.…”
Section: Discussioncontrasting
confidence: 62%
“…Indeed, data non-specific to smokers indicate that self-reported physical activity enjoyment is cross-sectionally positively correlated with level of physical activity engagement (Cleland et al, 2010; Hagberg et al, 2009; Rech et al, 2014; Salmon et al, 2003; Umeda et al, 2014) and prospectively associated with greater exercise program adherence and long-term maintenance of physical activity (Crain et al, 2010; Dishman et al, 2014; Herens et al, 2016; Lewis et al, 2016; Williams et al, 2006). Self-report of physical activity enjoyment also predicts acute increases in positive mood and decreases in negative mood from pre- to post- exercise (Miller et al, 2005; Motl et al, 2000) and mediates the exercise-mood relationship (Miller et al, 2005; Motl et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…An engagement in moderate physical activities is proven to be the key element of achieving a healthy and active lifestyle which is promoted by active aging [4,5]. The benefits of physical activities include the enhancement of body balance, strength, and mental health [6][7][8]. The physical activities discussed in this paper include active activities and passive activities.…”
Section: Introductionmentioning
confidence: 99%